2021
DOI: 10.1016/j.cell.2021.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic modulation of host development by ubiquitin-independent protein degradation

Abstract: Highlights d Phytoplasma SAP05 proteins bind plant SPL and GATA transcription factors and RPN10 d SAP05 mediates degradation of SPLs and GATAs in a ubiquitin-independent manner d SAP05 decouples plant developmental transitions and induces witches' broom symptoms d Engineering of plant RPN10 confers resistance to SAP05 activities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 75 publications
(113 reference statements)
5
105
0
Order By: Relevance
“…Comparison of putative effector gene content revealed that ‘ Ca . P. aurantifolia’ NCHU2014 harbors SAP11 ( Bai et al, 2009 ) and SAP54 ( MacLean et al, 2011 ) homologs while lacking homologs o SAP05 ( Huang et al, 2021 ) or TENGU ( Hoshi et al, 2009 ; Figure 7 and Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of putative effector gene content revealed that ‘ Ca . P. aurantifolia’ NCHU2014 harbors SAP11 ( Bai et al, 2009 ) and SAP54 ( MacLean et al, 2011 ) homologs while lacking homologs o SAP05 ( Huang et al, 2021 ) or TENGU ( Hoshi et al, 2009 ; Figure 7 and Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, protein degradation analysis revealed that MG132, a specific 26S proteasome, relieved the decrease level of ABI4 protein, indicating that ABI4 degradation was also regulated via the 26S proteasome pathway, which was also found in ABI1 and ABI5 [32,33]. However, a recent study has found that phytoplasma SAP05 (secreted AY-WB proteins) mediates the concurrent degradation of SPL and GATA developmental regulators via hijacking the plant ubiquitin receptor RPN10 independent of substrate ubiquitination [34]. Thus, the degradation of ABI4 may also not be dependent on ubiquitination entirely.…”
Section: Discussionmentioning
confidence: 70%
“…An important feature of phytoplasmas is their ability to modulate host plant development through effectors, which are small secreted proteins (Sugio et al, 2011b;Sugio and Hogenhout, 2012). To date, four phytoplasma effectors have been experimentally characterized, including SAP05 (Gamboa et al, 2019;Huang and Hogenhout, 2019;Huang et al, 2021), SAP11/SWP1 (Bai et al, 2009;Sugio et al, 2011a;Lu et al, 2014;Chang et al, 2018;Wang et al, 2018cWang et al, , 2018b, SAP54/PHYL1 (MacLean et al, 2011;Maejima et al, 2014;Orlovskis and Hogenhout, 2016), and TENGU (Hoshi et al, 2009;Sugawara et al, 2013;Minato et al, 2014). The expanded genome sequence availability allowed us to investigate the phylogenetic distribution of homologous effector genes among diverse phytoplasmas.…”
Section: Effector Genesmentioning
confidence: 99%